Development of neonatal brain functional centrality and alterations associated with preterm birth. (20th November 2022) - Fenn-Moltu, Sunniva; Fitzgibbon, Sean P; Ciarrusta, Judit; Eyre, Michael; Cordero-Grande, Lucilio; Chew, Andrew; Falconer, Shona; Gale-Grant, Oliver; Harper, Nicholas; Dimitrova, Ralica; Vecchiato, Katy; Fenchel, Daphna; et al.
Abstract: Formation of the functional connectome in early life underpins future learning and behavior. However, our understanding of how the functional organization of brain regions into interconnected hubs (centrality) matures in the early postnatal period is limited, especially in response to factors associated with adverse neurodevelopmental outcomes such as preterm birth. We characterized voxel-wise functional centrality (weighted degree) in 366 neonates from the Developing Human Connectome Project. We tested the hypothesis that functional centrality matures with age at scan in term-born babies and is disrupted by preterm birth. Finally, we asked whether neonatal functional centrality predicts general neurodevelopmental outcomes at 18 months. We report an age-related increase in functional centrality predominantly within visual regions and a decrease within the motor and auditory regions in term-born infants. Preterm-born infants scanned at term equivalent age had higher functional centrality predominantly within visual regions and lower measures in motor regions. Functional centrality was not related to outcome at 18 months old. Thus, preterm birth appears to affect functional centrality in regions undergoing substantial development during the perinatal period. Our work raises the question of whether these alterations are adaptive or disruptive and whether they predict neurodevelopmental characteristics that are more subtle or emerge later in life.